A Comprehensive Model of Prevention of Deviant Behavior through the Formation of a Positive and «Stable Self-Concept» (on the Example of Implementation in the Sverdlovsk Region) - Shempeleva, N.I.; Trifonova, N.I.; Bulatova, N.A. (Bulletin of Practical Psychology of Education, 2022)
The article describes a model for preventing deviant behavior among minors, which is being developed and implemented in the Sverdlovsk Region. The model presented is based on the concept of “Self-concept” as a relatively stable, to a greater or lesser degree perceived system of ideas of an individual about himself/herself, on the basis of which he/she treats him/herself and builds his/her interaction with other people. The purpose of the juvenile deviant behavior prevention model implementation is a steady decrease in the level of manifestation of such behavior and its early prevention. The basis for the confident achievement of this goal is the formation of a stable “Self-concept” in the juveniles. This model covers the period of personality formation from birth to adulthood and combines the efforts of parents, teachers, social workers and authorities in order to ensure the formation of personality with developed self-awareness, taking into account the need for intersystem and intradepartmental interaction, with mandatory monitoring of the effectiveness of goal achievement at all stages and timely corrective actions. Tools of prevention and early detection of juvenile behavioral disorders are early intervention services, advisory services, psychological-medical-pedagogical commissions, social-psychological testing. Thus, the model is equally aimed at working with minors at all stages of personality formation, as well as with parents and teachers directly involved in the process of personality formation. Herewith, for each of target groups within the limits of realization of the model the corresponding purposes and problems which solution provides controllable achievement of result are provided. В статье описана модель профилактики девиантного поведения несовершеннолетних, которая разрабатывается и реализуется на территории Свердловской области. В основе представленной модели лежит понятие «Я-концепция» как относительно устойчивая, в большей или меньшей степени осознаваемая система представлений индивида о самом себе, на основе которой он относится к самому себе и строит свое взаимодействие с другими людьми. Целью внедрения модели профилактики девиантного поведения несовершеннолетних является устойчивое снижение уровня проявлений такого поведения и его ранняя профилактика. Основой для уверенного достижения этой цели является формирование у несовершеннолетних устойчивой «Я-концепции». Данная модель охватывает период формирования личности от рождения до совершеннолетия и объединяет — в целях обеспечения формирования личности с развитым самосознанием — усилия родителей, педагогов, социальных работников и органов власти. При этом учитывается необходимость межсистемных и внутриведомственных взаимодействий и проводится обязательный мониторинг эффективности достижения цели на всех этапах, а также своевременные корректирующие действия. Инструменты профилактики и раннего выявления нарушений поведения несовершеннолетних это: служба ранней помощи, консультативные службы, психолого-медико-педагогические комиссии, социально-психологическое тестирование. Таким образом, модель равно нацелена на работу с несовершеннолетними на всех стадиях формирования личности, а также на родителей и педагогов, непосредственно участвующих в процессе становления личности. При этом для каждой из целевых групп в рамках реализации модели предусмотрены соответствующие цели и задачи, решение которых обеспечивает управляемое достижение результата.